2014
DOI: 10.3198/jpr2014.04.0020crc
|View full text |Cite
|
Sign up to set email alerts
|

Registration of ‘Chisholm’ Zoysiagrass

Abstract: Chisholm' (Reg. No. CV-273, PI 666039) is a zoysiagrass (Zoysia japonica Steud.) approved for release by Texas A&M AgriLife Research, Dallas, TX, and the Kansas Agricultural Experiment Station, Manhattan, KS. Chisholm is a clonal selection made in 1997 from a germplasm nursery established in 1983 in Dallas. It was originally evaluated under the designation TAES 4436 and included in the 2002 National Turfgrass Evaluation Program Zoysiagrass Variety Test under the designation DALZ 0102. Chisholm has a texture co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…KSUZ 0802 had higher plot coverage compared with Meyer in Wichita, KS, and Knoxville, TN. The average across all nine locations showed that the establishment of KSUZ 0802 (74.0%) was similar to both Chisholm (76.7%) and Meyer (67.2%), but Chisholm had a greater establishment rate than Meyer, which is in agreement with Chandra et al (2015). KSUZ 0802 and Chisholm were in the top statistical group in all nine locations, whereas Meyer was only a top performer in five of the locations.…”
Section: Characteristicssupporting
confidence: 72%
See 2 more Smart Citations
“…KSUZ 0802 had higher plot coverage compared with Meyer in Wichita, KS, and Knoxville, TN. The average across all nine locations showed that the establishment of KSUZ 0802 (74.0%) was similar to both Chisholm (76.7%) and Meyer (67.2%), but Chisholm had a greater establishment rate than Meyer, which is in agreement with Chandra et al (2015). KSUZ 0802 and Chisholm were in the top statistical group in all nine locations, whereas Meyer was only a top performer in five of the locations.…”
Section: Characteristicssupporting
confidence: 72%
“…Meyer is susceptible to bluegrass billbug injury, and Chisholm has been shown to exhibit excellent resistance (Chandra et al, 2015). Data collected at Manhattan, KS (Table 8; Fry and Cloyd, 2011), demonstrated that KSUZ 0802 had significantly less bluegrass billbug damage than Meyer in 2009 and 2010.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three releases resulted from these breeding efforts and include Diamond (Engelke et al, 2002a), Palisades (Engelke et al, 2002d), and Crowne (Engelke et al, 2002c). In 2007, Dr. Ambika Chandra assumed direction of this program and released Chisholm zoysiagrass in cooperation with Dr. Jack Fry at Kansas State University (Table 4) (Chandra et al, 2015). More recently, Texas A&M University and Kansas State University worked cooperatively to release KSUZ 0802, a dense, fine‐textured Z. matrella × Z. japonica hybrid that has cold hardiness comparable with Meyer (Table 4) (Chandra et al, 2017a).…”
Section: Improvementmentioning
confidence: 99%
“…'Chisholm' zoysiagrass is a suitable turfgrass for residential and commercial lawns, parks, and golf courses in the transition zone (Chandra et al, 2014). In Kansas, 'Chisholm' usually takes on a straw-brown color of dormancy in October and begins to greenup in mid to late April as noted in studies during its development when it was evaluated under the experimental designation DALZ0102 (Okeyo et al, 2011).…”
mentioning
confidence: 99%